2019
DOI: 10.1371/journal.pone.0215485
|View full text |Cite
|
Sign up to set email alerts
|

Simplification of vector communities during suburban succession

Abstract: Suburbanization is happening rapidly on a global scale, resulting in changes to the species assemblages present in previously undeveloped areas of land. Community-level changes after anthropogenic land-use change have been studied in a variety of organisms, but the effects on arthropods of medical and veterinary importance remain poorly characterized. Shifts in diversity, abundance, and community composition of such arthropods, like mosquitoes, can significantly impact vector-borne disease dynamics due to vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Our correlations of mosquito collections and land cover support previous short-term research on mosquito communities [13][14][15][16][17][18] : after accounting for surveillance effort, richness and evenness were highest in sites with a greater prevalence of forested land cover and lowest in sites with a greater prevalence of land cover associated with human developments. This trend in richness was further evident in our GLMMs of collections by latitudinal www.nature.com/scientificreports/ coordinate (which also reflect the dominant land cover gradient of urban to forested in CT).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Our correlations of mosquito collections and land cover support previous short-term research on mosquito communities [13][14][15][16][17][18] : after accounting for surveillance effort, richness and evenness were highest in sites with a greater prevalence of forested land cover and lowest in sites with a greater prevalence of land cover associated with human developments. This trend in richness was further evident in our GLMMs of collections by latitudinal www.nature.com/scientificreports/ coordinate (which also reflect the dominant land cover gradient of urban to forested in CT).…”
Section: Resultssupporting
confidence: 84%
“…There is some research that explores how mosquito communities are changing due to landscape-level dynamics. Previous studies on mosquito community structure have shown reductions in mosquito species richness and increases in the dominance of vectors of public health importance along forested to urban gradients 13 , simplification of mosquito community structure in homogenized landscapes 14 , changes in human risk of mosquito-borne pathogens linked to habitat disturbances 15,16 , and in some instances, increased mosquito species richness was associated with increased pathogen prevalence 17,18 . Globalization has also led to the introduction and establishment of mosquito species (and mosquito-borne pathogens) outside their evolutionary origins 19,20 .…”
mentioning
confidence: 99%
“…On a global scale, suburbanisation takes place relatively quickly in terms of time, which often results in relatively rapid changes in different fauna and flora societies due to anthropogenic interventions, and thus, induced changes in the area, which may cause changes which are very difficult to reverse, e.g., in terms of the diversity, abundance and overall composition of the society [31] and the structure of individual food chains [32]. Suburbanisation also extensively affects watercourses and their ecosystems, and the more populated the area (e.g., the higher the density of population and built-up areas, networking by transport and technical infrastructure), the more difficult and costly it is to restore watercourses [33].…”
Section: Suburbanisation In the Context Of Environmental Aspects And mentioning
confidence: 99%
“…Eleven questions (Table 2) were selected for this interview from studies that discussed the environmental impact of the suburbanisation process [21,[31][32][33][34]39,62], which were further divided into two categories. The first category included four questions concerning the territorial development of the municipality.…”
Section: Change In the Number Of Economic Entitiesmentioning
confidence: 99%
“…In this context, many citizen science projects successfully focus on mosquitoes (e.g. Bazin & Williams, 2018; Jordan et al., 2017; Kampen et al., 2015; Mwangungulu et al., 2016; Palmer et al., 2017; Spence Beaulieu et al., 2019), so that mosquito‐related programmes involving the public are being deployed in an increasing number of countries (e.g. Moore et al., 2019; Murindahabi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%